VD_FINDINFO Arrêt / 2019 / 295 vom 9. April 2019 - VD Tribunal cantonal (2019)
FRAIS DE VOYAGE, AA, FRAIS DE TRAITEMENT | 10 al. 1 LAA, 10 al. 1 let. a LAA, 13 al. 1 LAA, 21 al. 1 LAA, 48 LAA, 6 al. 1 LAA